Cyclosporine in acute ischemic stroke. (2nd June 2015) - Nighoghossian, Norbert; Berthezène, Yves; Mechtouff, Laura; Derex, Laurent; Cho, Tae Hee; Ritzenthaler, Thomas; Rheims, Sylvain; Chauveau, Fabien; Béjot, Yannick; Jacquin, Agnès; Giroud, Maurice; Ricolfi, Frédéric; et al.
Abstract : Objectives: We examined whether IV administration of cyclosporine in combination with thrombolysis might reduce cerebral infarct size. Methods: Patients aged 18 to 85 years, presenting with an anterior-circulation stroke and eligible for thrombolytic therapy, were enrolled in this multicenter, single-blinded, controlled trial. Fifteen minutes after randomization, patients received either an IV bolus injection of 2.0 mg/kg cyclosporine (Sandimmune, Novartis) or placebo. The primary endpoint was infarct volume on MRI at 30 days. Secondary endpoints included infarct volume according to the site (proximal/distal) of arterial occlusion and recanalization after thrombolysis. Results: From October 2009 to July 2013, 127 patients were enrolled. The primary endpoint was assessed in 110 of 127 patients. The reduction of infarct volume in the cyclosporine compared with the control group was overall not significant (21.8 mL [interquartile range, IQR 5.1, 69.2 mL] vs 28.8 mL [IQR 7.7, 95.0 mL], respectively; p = 0.18). However, in patients with proximal occlusion and effective recanalization, infarct volume was significantly reduced in the cyclosporine compared with the control group (14.9 mL [IQR 1.3, 23.2 mL] vs 48.3 mL [IQR 34.5, 118.2 mL], respectively; p = 0.009). Conclusions: Cyclosporine was generally not effective in reducing infarct size. However, a smaller infarct size was observed in patients with proximal cerebral artery occlusion and efficient recanalization. Classification of evidence: This study provides Class I evidence that in patients with an acute anterior-circulation stroke, thrombolysis plus IV cyclosporine does not significantly decrease 30-day MRI infarct volume compared with thrombolysis alone.